2018
DOI: 10.1038/s41467-018-03591-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase nucleation through confined spinodal fluctuations at crystal defects evidenced in Fe-Mn alloys

Abstract: Analysis and design of materials and fluids requires understanding of the fundamental relationships between structure, composition, and properties. Dislocations and grain boundaries influence microstructure evolution through the enhancement of diffusion and by facilitating heterogeneous nucleation, where atoms must overcome a potential barrier to enable the early stage of formation of a phase. Adsorption and spinodal decomposition are known precursor states to nucleation and phase transition; however, nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 65 publications
2
51
0
Order By: Relevance
“…This topical Frontier's edition contains more details about this structure obtained along additive manufacturing routes with post-build annealing, as described by D. Vogiatzief et al and V. Rocio Molina Ramirez et al We point out, that nucleation triggered by the compositional modulations of a spinodal decomposition occurs in Fe-Mn alloys, being confined to crystalline defects (Da Silva et al, 2018). Furthermore, Loh et al, 2017 reported spinodal decomposition as the first step in a multistep nucleation of gold and silver nanocrystals in aqueous solutions.…”
Section: Dual-phase Microstructures and Associated Phase Transformatimentioning
confidence: 99%
“…This topical Frontier's edition contains more details about this structure obtained along additive manufacturing routes with post-build annealing, as described by D. Vogiatzief et al and V. Rocio Molina Ramirez et al We point out, that nucleation triggered by the compositional modulations of a spinodal decomposition occurs in Fe-Mn alloys, being confined to crystalline defects (Da Silva et al, 2018). Furthermore, Loh et al, 2017 reported spinodal decomposition as the first step in a multistep nucleation of gold and silver nanocrystals in aqueous solutions.…”
Section: Dual-phase Microstructures and Associated Phase Transformatimentioning
confidence: 99%
“…The reason for this electrical passivation might be the abovementioned atomic redistribution and segregation of alkali metals. 72 .…”
Section: Segregation In Cigsmentioning
confidence: 99%
“…In Figure 7 (a), the structural information extracted from the partial crystallographic information available within the detector hit maps shown in (a) allow for full misorientation determination 27,29,33 . Figure 7 At 450°C, a miscibility gap in the FeMn appears in the phase diagram that can lead to a spinodal decomposition 72 . As the local composition of a microstructural feature reaches a certain threshold composition, compositional fluctuations along the linear defects and planar defects can be interpreted as a confined spinodal fluctuations.…”
Section: Phase Nucleation At Crystalline Defectsmentioning
confidence: 99%
“…GBs are a type of lattice imperfection [1,2], with their own structure and composition, and as such impact a material's mechanical and functional properties [3]. Structural motifs and phases formed at chemically decorated GBs can be of a transient nature [4][5][6][7] or are local thermodynamic structural-chemical equilibrium states [8][9][10][11]. General GBs exhibit a wide range of local crystallographic structure and facet motifs.…”
mentioning
confidence: 99%